Antibacterial Effect of Photodynamic Therapy on Root Canal Disinfection Combined with Different Irrigation Protocols - Neves, Gabriella de Vasconcelos; Santos, Kátia Simone Alves dos; Rocha, Eveline Angélica Lira de Souza Sales; Moura, Rodrigo Queiroga de; Barros, Danyllo Guimarães Morais; Gominho, Luciana Ferraz; Gomes, Daliana Queiroga de Castro (Iranian Endodontic Journal, 2020)
Introduction: Photodynamic therapy (PDT) is an emerging alternative therapy to conventional endodontic treatment to optimize bacterial elimination. The aim of this study was to evaluate the in vitro antibacterial effect of PDT combined with different irrigation protocols on root canals inoculated with Enterococcus (E.) faecalis. Methods and Materials: Ninety uni-radicular human premolars were prepared and contaminated with E. faecalis for 4 days. Teeth were randomly divided into six groups: positive control group (C+) consisted of conventional needle irrigation with 2.5% sodium hypochlorite (NaOCl); negative control group (C-) consisted of no treatment after contamination; PDT group as treated with 0.005% methylene blue and diode laser irradiation for 90 sec at wavelength of 660 nm, energy of 9 Joules, power of 100 mW; the fourth group consisted of NaOCl+PDT, the fifth group were treated with passive ultrasonic irrigation (PUI) with NaOCl+PDT (PUI+PDT); and the final group were treated with XP Endo Finisher with NaOCl+PDT (XP Endo+PDT). The contents of the root canals were collected with sterile absorbent paper points at two times: before and 24 h after decontamination protocols. The number of colony-forming units (CFU) was determined for each root canal. ANOVA and the Tukey test were used, with significance set at 5% (P<0.05). Results: The inhibition percentage ranged from 10.72 (C-) to 100% (XP Endo+PDT), with CFU/mL counts differing among all protocols tested (P<0.05). The different protocols significantly influenced bacterial inhibition (P<0.05). However, the XP Endo+PDT protocol resulted in the highest inhibition percentage (100%), followed by NaOCl+PDT (65.85%). Conclusions: PDT combined with different final irrigation protocols was more effective in inhibiting E. faecalis growth than photodynamic therapy alone. XP Endo was the best irrigation protocol to eradicate this microorganism. Keywords: Biofilm; Endodontics; Enterococcus faecalis; Photodynamic Therapy